Pengaruh Sikap Wajib Pajak, Kesadaraan Wajib Pajak, Pengetahuan Pajak Sanksi Perpajakan, dan Akuntabilitas Pelayanan Publik terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Samsat Tanjung Kabupaten Brebes - Yuniarti Herwinarni; Antika Reza Anggraeni (Faculty of Economics and Business, University of Pancasakti Tegal, 2016)
The purpose of this study is for know the influence of attitudes the taxpayer, taxpayer, awareness, knowledge taxes, sanctions taxastion and accountability public service against taxpayer compliance in paying taxes motor vehicle. The research was conducted at the SAMSAT Tanjung City. The number of samples in this research is as many as 100 respondents with method sampling using slovin formula. Data collection is done through interviews, questionnaire and observation. Technical analysis of data who worn in the researching this is multiple liniear regression. Based of the result of analysis then it can be known that the parsial attitude the taxpayer does not significantly effect taxpayer compliance in paying taxes motor vehicle, tax payer awareness significantly effect taxpayer compliance in paying taxes motor vehicle office SAMSAT Tanjung City, knowledge taxes not significantly effect taxpayer compliance in paying taxes motor vehicle, sanctions taxastion not significantly effect taxpayer compliance in paying taxes motor vehicle, accountability public service significantly effect taxpayer compliance in paying taxes motor vehicle office SAMSAT Tanjung City. And simultaneously the tax payer attitudes, the taxpayer, taxpayer awareness, knowledge taxes, sanctions taxastion and accountability public service, significantly effect taxpayer compliance in paying taxes motor vehicle office SAMSAT Tanjung City.